β-lactam antibiotics epitope mapping with STD NMR spectroscopy: A study of drug-human serum albumin interaction - Milagre, Cíntia D. F. [UNESP]; Cabeça, Luís F.; Almeida, Wanda P.; Marsaioli, Anita J. (FapUNIFESP (SciELO), 2012)
Molecular recognition events are key issues in many biological processes. STD NMR (saturation transfer difference nuclear magnetic resonance spectroscopy) is one of the techniques used to understand such biological interactions. Herein, we have investigated the interactions of four β-lactam antibiotics belonging to two classes (cephalosporins and penicillins) with human serum albumin (HSA) by 1H STD NMR revealing that the interaction between the aromatic moiety and HSA is responsible for the binding efficiency. Thus, the structural differences from the five to six-membered thio ring in penicillins and cephalosporins do not seem to influence antibiotic-albumin interactions. © 2012 Sociedade Brasileira de Química.
Keywords: β-lactam antibiotics; Albumin; Ligand-macromolecules interaction; STD NMR